2019
DOI: 10.3390/medicines6040110
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dysregulated Ion Channels in Sensory Neurons in Chronic Kidney Disease-Associated Pruritus

Abstract: Background: We investigated ion channels at the skin, including peripheral nerve endings, which serve as output machines and molecular integrators of many pruritic inputs mainly received by multiple G protein-coupled receptors (GPCRs). Methods: Based on the level of chronic kidney disease–associated pruritus (CKD-aP), subjects were divided into two groups: non-CKD-aP (no or slight pruritus; n = 12) and CKD-aP (mild, moderate, or severe pruritus; n = 11). Skin samples were obtained from the forearm or elbow dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…This is particularly the case for patients on dialysis who frequently suffer from uremic itch, with about 40% of patients with end-stage renal disease being afflicted with moderate to severe pruritus [ 15 ]. In this context it is interesting to note that Cav3.2 channel expression is upregulated in the skin of uremic itch patients (presumably in nerve endings) [ 16 ], hinting at a possible role of these channels in uremic itch pathology. While we did not examine mouse models of chronic pruritus here, there is accumulating evidence that Cav3.2 channels are involved in the development of histamine and non-histamine dependent itch in rodents.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly the case for patients on dialysis who frequently suffer from uremic itch, with about 40% of patients with end-stage renal disease being afflicted with moderate to severe pruritus [ 15 ]. In this context it is interesting to note that Cav3.2 channel expression is upregulated in the skin of uremic itch patients (presumably in nerve endings) [ 16 ], hinting at a possible role of these channels in uremic itch pathology. While we did not examine mouse models of chronic pruritus here, there is accumulating evidence that Cav3.2 channels are involved in the development of histamine and non-histamine dependent itch in rodents.…”
Section: Resultsmentioning
confidence: 99%
“…They found a significantly elevated expression of Cav3.2, BKCa, and anoctamin1, and reduced expression of TRPV1 in CKD-aP patients. They concluded that these changes in expression of ion channels in CKD patients might increase generator potential related to itching [ 31 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Chronic kidney disease-associated pruritus CKD-aP is thought to involve an alteration in nerve fibers and increased amounts of circulating pruritogens such as uremic toxins, which also stimulate reactive oxygen species (ROS) [26]. One study sought to further understand how the interact between uremic toxins and nerve fibers in patients with CKD-aP resulted in itch [27]. Momose et al obtained skin biopsies from the forearm and elbow of two cohorts of patients.…”
Section: Pathophysiologymentioning
confidence: 99%